Identifying Coping Mechanisms of Exam Anxiety as Innovative Technique to Prepare Malaysian Secondary School Students for Examination - Surat, Shahlan; Nabilah Mohammad Khalipah, Nurul; Ramli, Shalinawati; Baharudin, Harun; Yazid Abu Bakar, Abu; ., Sasmoko (International Journal of Engineering and Technology, 2018)
The study aims to determine the level of exam anxiety and the coping mechanisms used by the students, and also the relationship between the two variables. This is due to the fact that highly suitable and effective exam anxiety coping mechanisms are believed to be able to help the students in overcoming their anxiety. The study used the survey method in order to find out the anxiety level and the coping mechanisms used by the students in handling exam anxiety. 324 Form Four students from a daily secondary school (152 male, 172 female) were selected as the study sample. The instruments utilized in the study were the questionnaires of Test Anxiety Inventory, also known as TAI Inventory, and Coping with Pre-Exam Anxiety and Uncertainty (COPEAU). The results indicated that the exam anxiety level of the students was moderate. Also, there is a significant difference level of exam anxiety and the coping mechanisms based on genders, in which the mean value for female students is much higher than that of male students. From the aspect of coping mechanisms, it was found that a large number of the secondary school students used the task-orientation and preparation and also seeking social support as the mechanisms in handling anxiety, while only a few of them used the avoidance mechanism. The implication of preparing the students prior to the examination was discuss.Â Â
Keywords: Coping mechanisms; exam anxiety; Malaysian secondary education